2021
DOI: 10.1007/s11136-021-02889-z
|View full text |Cite
|
Sign up to set email alerts
|

Beyond viral suppression: Quality of life among stable ART clients in a differentiated service delivery intervention in Tanzania

Abstract: Background With antiretroviral therapy, more people living with HIV (PLHIV) in resource-limited settings are virally suppressed and living longer. WHO recommends differentiated service delivery (DSD) as an alternative, less resource-demanding way of expanding HIV services access. Monitoring client’s health-related quality of life (HRQoL) is necessary to understand patients’ perceptions of treatment and services but is understudied in sub-Saharan Africa. We assessed HRQoL among ART clients in Tanz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(91 reference statements)
1
1
0
Order By: Relevance
“…We observed no significant differences in acceptability with care between study arms or when comparing participants who entered DSD and those who did not, suggesting that early DSD is acceptable to Rwandan PWH. Our results are similar to research showing similar quality of life among people enrolled in DSD and those in traditional models [ 26 ], although some studies have described lower satisfaction with care among patients in DSD models for shorter compared to longer periods of time [ 27 ]. We found that acceptability did not differ between study arms or between those enrolled in DSD and those in TAU, suggesting that differences were not related to frequency of encounters.…”
Section: Discussionsupporting
confidence: 90%
“…We observed no significant differences in acceptability with care between study arms or when comparing participants who entered DSD and those who did not, suggesting that early DSD is acceptable to Rwandan PWH. Our results are similar to research showing similar quality of life among people enrolled in DSD and those in traditional models [ 26 ], although some studies have described lower satisfaction with care among patients in DSD models for shorter compared to longer periods of time [ 27 ]. We found that acceptability did not differ between study arms or between those enrolled in DSD and those in TAU, suggesting that differences were not related to frequency of encounters.…”
Section: Discussionsupporting
confidence: 90%
“…While PLHIV in high-income countries (HIC) reports signi cantly lower health-related quality of life than the general population, research on HRQoL of PLHIV in low-and middle-income countries (LMIC) is limited (21). Based on these concerns, there is the need to conduct a study to evaluate the quality of life of people living with HIV on differentiated service delivery and to determine the sociodemographic predictors of 'no problems' in PLHIV in a South-eastern Nigerian State.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries around the world have adopted the test-and-treat strategy for managing HIV treatment as recommended by WHO [2,3]. This implementation has contributed to improvement of viral suppression and has been associated with a reduced risk of HIV transmission, better quality of life, and increased life expectancy in people living with HIV [4][5][6][7]. Despite this overwhelming evidence, UNAIDS estimates that only 81% of pregnant women accessed antiretroviral drugs in 2021 to prevent transmission of HIV to their children [1].…”
Section: Introductionmentioning
confidence: 99%